Creatine kinase and its muscle/brain isoenzyme as potential biomarkers for cardiovascular disease risk: A cross-sectional analysis of a population-based cohort - Mahla Izadpanah; Elahe Pourahmadi; Hamideh Safarian Bana; Elham Dehghani; Masoumeh Akbari; Fatemeh Asgharian Rezae; Fatemeh Yarmohammadi; Ashraf Alnattah; Saeid Eslami; Zhila Taherzadeh (PLoS ONE, 2025)
Introduction This study examines the correlation between creatine kinase (CK) and its muscle/brain isoenzyme (CK-MB) in relation to cardiovascular risk factors, highlighting sex disparities. Methods A three-year cross-sectional study was conducted among 246 adults recruited from the Mashhad University of Medical Sciences (MUMS) Persian Cohort. CK and CK-MB concentrations were measured using standardized laboratory assays. Correlations and multivariable linear models were used to assess associations with cardiovascular risk indicators. Results Men exhibited significantly higher log-transformed CK and CK-MB levels than women. Both enzymes showed weak-to-moderate correlations with selected cardiovascular parameters. Log CK was modestly associated with diastolic blood pressure (DBP), creatinine, and PWV (r < 0.29), whereas log CK-MB showed positive associations with calcium, potassium, DBP, and PWV. Many univariable associations attenuated after adjustment, with only serum calcium remaining independently related to log CK-MB (p = 0.03). Conclusion In this cross-sectional cohort, log CK and log CK-MB showed weak but statistically detectable associations with selected cardiovascular measures. These findings are hypothesis-generating and should be interpreted cautiously; they do not support clinical recommendations without prospective validation in larger studies.